Impetigo herpetiformis with postpartum flare-up - Roth, Maria-Magdalena (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
Impetigo herpetiformis is a rare dermatosis of pregnancy with typical onset during the last trimester of pregnancy and rapid resolution during the postpartum period. It is still a matter of debate whether it is a variant of pustular psoriasis or a separate entity. We report a case of impetigo herpetiformis with an earlier onset during the second trimester of pregnancy (G4 P2) and an atypical postpartum flare-up. Even though the case is not new per se, it reveals the natural course of this rare disease because the condition was neglected and given no oral treatment throughout the entire pregnancy. Consequently, the patient had a premature delivery with premature rupture of membranes, placental insufficiency, and intrauterine growth retardation.
Keywords: dermatoze; human pregnancy; impetigo; nosečnost